CircRNA-based AntimiR therapy: A novel approach to hypertension treatment - Vahideh Tarhriz; Kamran Hosseini; Leila Abkhooie; Eric Lazartigues (Non-coding RNA Research)
The increasing recognition of the types and functions of non-coding RNAs has opened new avenues for their use as novel therapeutic strategies in the treatment of chronic diseases such as hypertension. While most preclinical and clinical studies on hypertension focus on prognosis and treatment, there are still no specific therapeutic approaches for primary and essential hypertension. Modest efficacy and reduced long-term adherence to treatment underscore the need for novel, mechanism-based strategies to address the underlying molecular mechanisms. AntimiRs, as synthetic RNA molecules, and circular RNAs (circRNAs), as naturally occurring RNA species that function as microRNA sponges, could play a crucial role in regulating the renin-angiotensin system (RAS). These non-coding RNAs hold significant potential as innovative approaches for managing primary and essential hypertension. This review aims to provide a comprehensive overview of circRNA-miRNA interactions involved in hypertension regulation via modulation of the RAS, their mechanisms of action, therapeutic advantages, and the major translational challenges, including delivery efficiency, off-target effects, and safety concerns. Optimization of the delivery systems, validating long-term efficacy, and navigating regulatory pathways to bring these promising ncRNA-based therapies closer to preclinical and clinical research of antimiR-based therapies are addressed. Furthermore, this review highlights the potential of these new RNA targets to fill the current therapeutic void and contribute to the advancement of precision medicine in hypertension and related cardiovascular diseases treatment.